2021
DOI: 10.3201/eid2710.211265
|View full text |Cite
|
Sign up to set email alerts
|

New Delhi Metallo-β-Lactamase–Producing Enterobacterales Bacteria, Switzerland, 2019–2020

Abstract: Carbapenemase-producing Enterobacterales (CPE) bacteria are a critical global health concern; New Delhi metallo-β-lactamase (NDM) enzymes account for >25% of all CPE found in Switzerland. We characterized NDM-positive CPE submitted to the Swiss National Reference Center for Emerging Antibiotic Resistance during a 2-year period (January 2019–December 2020) phenotypically and by using whole-genome sequencing. Most isolates were either Klebsiella pneumoniae (59/141) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Carolina and her colleagues have proved that NDM is of a unique structure and located at the membrane, and these features confer its lowest fitness cost among a series of classical MBLs ( 8 , 31 ). Furthermore, while it has been reported that plasmids carrying bla NDM often co-harbor the resistance genes to aminoglycosides ( 32 , 33 ), we discovered that the majority of bla NDM -positive isolates from children were amikacin-susceptible.…”
Section: Discussionmentioning
confidence: 73%
“…Carolina and her colleagues have proved that NDM is of a unique structure and located at the membrane, and these features confer its lowest fitness cost among a series of classical MBLs ( 8 , 31 ). Furthermore, while it has been reported that plasmids carrying bla NDM often co-harbor the resistance genes to aminoglycosides ( 32 , 33 ), we discovered that the majority of bla NDM -positive isolates from children were amikacin-susceptible.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, the resistance patterns of Enterobacterales with the NDM enzyme present extensive resistance to β-lactam antibiotics and are not inhibited by β-lactamase inhibitors, except for aztreonam. However, especially when co-expression is present, some studies have shown that there are remarkable associations between bla NDM genes and multiple other resistance genes, such as genes encoding extended-spectrum β-lactamases (ESBLs), AmpC, or other classes of carbapenemases (KPCs) that may lead to resistance to aztreonam [ 21 ]. Additionally, combination with ribosomal rRNA methylases (16S-RMTases) can confer a high level of resistance to all aminoglycosides [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Switzerland, from the isolates submitted to the Swiss National Reference Center for Emerging Antibiotic Resistance for 2 years (January 2019–December 2020), among the 108 sequenced isolates, NDM-1 was the most prevalent variant, occurring in 56 isolates, mostly K. pneumoniae isolates (34/56); the following most prevalent variant was NDM-5, which occurred in 49 isolates, mainly E. coli isolates (40/49) ( Findlay et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%